Temporal Dynamics of Host Immune Response Associated With Disease Severity and Time to Recovery in Patients Hospitalized for COVID-19. (7th September 2022) - Sophonsri, Anthony; Le, Diana; Lou, Mimi; Ny, Pamela; Minejima, Emi; Chambliss, Allison B.; Nieberg, Paul; Shriner, Kimberly; Wong-Beringer, Annie
Abstract : OBJECTIVES: The objective of this study was to compare the temporal dynamics of two viral-induced inflammatory proteins interferon gamma inducible protein-10 (IP-10) and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), as well as C-reactive protein (CRP) among patients hospitalized for COVID-19 and examine their prognostic significance. DESIGN: Prospective observational cohort study. SETTING: Multicenter, inpatient. PATIENTS: Adult patients infected with severe acute respiratory syndrome coronavirus 2 between March 2021 and October 2021. INTERVENTIONS: Patient sera were collected on days 1, 3, 5, and 7 of hospitalization. Levels of IP-10, TRAIL, and CRP were measured using a point-of-need diagnostic immunoassay platform (MeMed BV, MeMed, Haifa, Israel) and compared between patients grouped by disease severity (severe vs nonsevere). MEASUREMENTS AND MAIN RESULTS: Baseline characteristics were similar regardless of severity except for a higher prevalence of diabetes and heart failure among severe patients. The immune profile at admission was similar between groups; IP-10 and CRP levels generally decreased while TRAIL levels increased over time in all patients. However, the severe group had higher IP-10 (median 713 vs 328 pg/mL; p = 0.045) and lower TRAIL levels (median 21 vs 30 pg/mL; p = 0.003) on day 3 compared with nonsevere patients. A breakpoint IP-10 level of greater than or equal to 570 pg/mL and TRAIL level of less than 25 pg/mL on day 3 were associated with COVID-19 severity. Patients with elevated day 3 IP-10 levels (≥ 570 pg/mL) were more likely to experience prolonged recovery time (median 12 vs 3 d; p < 0.001). The severe group had prolonged use of corticosteroids (12 vs 5 d; p < 0.001) and had a higher rate of secondary infections (20% vs 6%; p = 0.04) and in-hospital mortality (20% vs 0%; p < 0.001) as compared with nonsevere patients. CONCLUSIONS: The observed patterns in host immune response revealed a turning point in COVID-19 disease on hospital day 3 and the potential utility of IP-10 and TRAIL as sensitive markers associated with disease severity and time to recovery.